Kurangnya Etika Dalam Lingkungan Keluarga - Nur Ayisah hutabarat; Novena Silitonga (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
Ethics is a form of human behavior that is considered good in the eyes of humans which is a benchmark for whether someone in their environment is good or not. The family is one of the smallest social spheres owned by each individual. Although in a small scope, the relationships that are built between family members are closer and more intimate. This is none other than because the family is a group of people who are bound by blood relations. Ethics in the family is something that really underlies the life of individuals in society, because all good and bad human behavior is basically created in the family environment because an individual is born and lives his first life. in the family environment. Then the family becomes the main actor of an individual to have good ethics. The purpose of the research is to improve ethics and manners in the family environment. The researcher uses a quantitative research method in the form of a questionnaire containing 10 data given to 13 samples. After conducting the research, the research team concluded that there is still a lack of ethics in the family, especially for those who do not live with their families.